Clinical Factors Associated with the Non-Operative Airway Management of Patients with Robin Sequence - Albino, Frank P.; Wood, Benjamin C.; Han, Kevin D.; Yi, Sojung; Seruya, Mitchel; Rogers, Gary F.; Oh, Albert K. (Archives of Plastic Surgery, 2016)
Background The indications for surgical airway management in patients with Robin sequence (RS) and severe airway obstruction have not been well defined. While certain patients with RS clearly require surgical airway intervention and other patients just as clearly can be managed with conservative measures alone, a significant proportion of patients with RS present with a more confusing and ambiguous clinical course. The purpose of this study was to describe the clinical features and objective findings of patients with RS whose airways were successfully managed without surgical intervention.Methods The authors retrospectively reviewed the medical charts of infants with RS evaluated for potential surgical airway management between 1994 and 2014. Patients who were successfully managed without surgical intervention were included. Patient demographics, nutritional and respiratory status, laboratory values, and polysomnography (PSG) findings were recorded.Results Thirty-two infants met the inclusion criteria. The average hospital stay was 16.8 days (range, 5–70 days). Oxygen desaturation (<70% by pulse oximetry) occurred in the majority of patients and was managed with temporary oxygen supplementation by nasal cannula (59%) or endotracheal intubation (31%). Seventy-five percent of patients required a temporary nasogastric tube for nutritional support, and a gastrostomy tube placed was placed in 9%. All patients continued to gain weight following the implementation of these conservative measures. PSG data (n=26) demonstrated mild to moderate obstruction, a mean apneahypopnea index (AHI) of 19.2±5.3 events/hour, and an oxygen saturation level <90% during only 4% of the total sleep time.Conclusions Nonsurgical airway management was successful in patients who demonstrated consistent weight gain and mild to moderate obstruction on PSG, with a mean AHI of <20 events/hour.
Keywords: Pierre robin syndrome; Classification; Disease management